Early prevention of cognitive impairment in the community population: The Beijing Aging Brain Rejuvenation Initiative. Issue 10 (31st March 2021) - Yang, Caishui; Li, Xin; Zhang, Junying; Chen, Yaojing; Li, He; Wei, Dongfeng; Lu, Peng; Liang, Ying; Liu, Zhen; Shu, Ni; Wang, Fang; Guan, Qing; et al.
Abstract: Facing considerable challenges associated with aging and dementia, China urgently needs an evidence‐based health‐care system for prevention and management of dementia. The Beijing Aging Brain Rejuvenation Initiative (BABRI) is a community‐based cohort study initiated in 2008 that focuses on asymptomatic stages of dementia, aims to develop community‐based prevention strategies for cognitive impairment, and provides a platform for scientific research and clinical trials. Thus far, BABRI has recruited 10, 255 participants (aged 50 and over, 60.3% female), 2021 of whom have been followed up at least once at a 2‐ or 3‐year interval. This article presents aims and study design of BABRI; summarizes preliminary behavioral and neuroimaging findings on mild cognitive impairment (MCI) and results of clinical trials on MCI; and discusses issues concerning early prevention in community, MCI diagnosis methods, and applications of database of aging and dementia. BABRI is proposed to build a systematic framework on brain health in old age.